OS CURRÍCULOS DE CASCAVEL (PR) E BAURU (SP) À LUZ DA PEDAGOGIA HISTÓRICO-CRÍTICA: UMA ANÁLISE DO ENSINO DE GEOGRAFIA - Moraes, Pauliane Goncalves (2020)
The object of study of this research was the relation between the teaching of geography and the school education curriculum, having as empirical references the curriculums of Cascavel (PR) and Bauru (SP). The aim was to evaluate the advances and limits of